Introversion-extraversion and the role of the orienting reaction habituation rate in sensitivity to the apparent size of hue - Bourgeois, Robert Paul (University of Ottawa (Canada), 1973)
Abstract not available.
Keywords: Psychology, Behavioral.; Psychology, Personality.